The Word Ummi And Its Derivation In The Qur'an (Semantic Analysis) - Anwar , Rahmah; Abdullah, Abdullah (Language Development Center, 2022)
Background: The word Ummi originally meant someone who was not good at reading and writing which happened in the jahiliyah era or what is known as the age of ignorance, but this word has other meanings. Purpose: this study aims to find out the word Ummi and its derivation in the Qur'an. Method: In this study, the researcher used a qualitative type of research using a descriptive approach, which by being described in the form of words and language, in a special natural context and by utilizing various scientific methods. Results and Discussion: In this study, it was revealed that the word Ummi and its derivation in the Qur'an when viewed from each verse of the Qur'an with all its derivations into two groups. The first group is some of the scholars of the book, found in surah al-Baqarah verse 78. The Second Group are people outside the scribes, which is meant those who are outside the scribes meaning people who do not believe in the books that are returned to the prophets who have received revelation from allah swt before the prophet Muhammad Saw. Conclusions and Implications: The word Ummi and its derivation in the Qur'an when viewed from each verse of the Qur'an with all its derivations into two groups. The first group is some of the scholars of the book, found in surah al-baqarah verse 78. The second group is people outside the scribes, which is meant people who are outside the scribes meaning people who do not believe in the books that are returned to the prophets who have received revelation from Allah SWT before the prophet Muhammad saw. The implications of this research are the importance of understanding the complexity and depth of the meaning of the word